Microstructural evaluation of CoAl2O4 nanoparticles by Williamson–Hall and size–strain plot methods - H. Irfan; Mohamed Racik K.; S. Anand (Journal of Asian Ceramic Societies, 2018)
CoAl2O4 nanoparticles were prepared by a Pechini method using chelating agent citric acid. CoAl2O4 nanoparticles were synthesized at different calcination temperatures of 600–900°C. The crystalline spinel cubic phase was confirmed by X-ray diffraction results. High-resolution scanning electron microscopy (HRSEM) revealed that nanoparticles of CoAl2O4 morphology showed spherical forms with a certain degree of agglomeration. The Williamson–Hall (W–H) method and size–strain method to evaluate the size of crystallites and strain in the CoAl2O4 nanoparticles’ peak broadening were applied. Physical parameters such as strain and stress values were calculated for all XRD reflection peaks corresponding to the cubic spinel phase of CoAl2O4 in the range of 20–70° from the modified plot shape by the W–H plot assuming a uniform deformation model (UDM), uniform stress deformation model (USDM), uniform deformation energy density model (UDEDM), and by the size–strain plot (SSP) method. The crystal size of the CoAl2O4 NPs calculated on the W–H plots and the SSP method are in good agreement with the HRSEM and Scherrer method.